Adoption of the performance measurement system in the Nigerian public sector: Challenges and prospects - Abubakar, Abdulkadir; Saidin, Siti Zabedah; Ahmi, Aidi (2015)
Assessing the performance of organizations using the performance measurement system has gradually become a common practice in the public sector entities.This has been established to be a direct fall out of the ripple effect of the new public management (NPM).Adoption of the performance measurement system in the public sector world over (not particularly in Nigeria) has been experiencing a myriad of challenges.This is imperative to point out owing to the fact that, the processes of adoption have been difficult, monotonous and time-consuming.In some public sector organizations where the adoption has been successful, such feat was achieved after intense difficulties, trial and error.In Nigeria, for instance, the analytical challenges in the adoption of the performance measurement system are too apparent to be ignored. Conversely, it is quite interesting to highlight that, in some countries, the development of measures to manage and evaluate public sector performance has reached a strategic height, therefore tracking of output, outcomes and input have been reasonably straightforward and significant progress is somewhat recorded.Finally, it is a general consensus among the public sector managers and academia that, adoption of the system of performance measurement in the public sector is a powerful tool that guarantees improved performance, quality of decision making and service delivery.